Sárköz – Alsónyék, Ungarn. Die Arbeiten der Jahre 2016 bis 2018 - Bánffy, Eszter (e-Forschungsberichte des DAI, 2018)
The south western edge of Transdanubia, in between the riverine alluvial landscape of the Danube and the first slopes of the Szekszárd hills, the happy coincidence of planned archaeological research projects (at Fajsz) and contract archaeological work prior to the building of the M6 motorway led to a large joint project, in cooperation of the Romano-Germanic Commission, Frankfurt, the Budapest Research Unit (Forschungsstelle) of the RGK and the Institute of Archaeology, RCH of the Hungarian Academy of Sciences. The region was a continuous scene for impacts from the onset of the Early Neolithic to the Copper Age, in the total of the 6th and 5th millennia cal BC. The evaluation involves several ongoing and already finalised MA and PhD programmes. The 4th year of our project made progress in the chronology of the late Neolithic Lengyel culture burials adjacent to the Alsónyék site; material analyses of the settlement pottery, the architecture of the Starčevo and the Lengyel settlements and a complex investigation of the chipped stone tools of the Alsónyék Lengyel settlement. The first volume on the environmental history of the Sárköz has also been completed.